Fission-track thermochronological evidence for the Yanshanian tectonic evolution of the northern Junggar Basin, northwest China - Li, Zhenhua; Chen, Zhanjun; Fan, Yuhai; Yu, Lan; Zhang, Suya; Li, Xiangyang (Frontiers in Earth Science, 2023)
The Junggar Basin is a multicycle intracontinental sedimentary basin developed on a pre-Mesozoic deformed basement. For a long time, the Junggar Basin and its adjacent Altai orogeny has being a focus of debate for geologists studying the opening and closing history of the Paleozoic Asian Ocean and Cenozoic intracontinental deformation. However, research on the intracontinental tectonic activities of northern Xinjiang since the Mesozoic, especially the Yanshanian tectonic activities in northern Junggar Basin, is not detailed. Fission track (FT) dating was conducted on 15 apatite samples and 8 zircon samples from the northern Junggar Basin to better understand the Yanshanian tectonic evolution and its peak age. The results showed that apatite FT (AFT) ages ranged from 131 to 42 Ma, and zircon FT ages ranged from 205 to 132 Ma. Combined with AFT track thermal history modeling and regional geological data, we proposed that the northern Junggar Basin underwent three periods of tectonic thermal events 165–161, 93–81, and 72–66 Ma. The thermal events of 165–161 Ma may indicate magmatic activity during the Yanshanian, while the 93–86 and 72–66 Ma events reflect Late Cretaceous uplift and cooling. This study, using thermochronology, has confirmed the tectonic evolution of Yanshanian in northern Junggar Basin. It has also revealed that the Yanshanian orogeny, a regional tectonic event, may also occurred in northwest China.